2020
DOI: 10.1039/c9ra05866d
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic investigations on the healing and softening of damaged salt by uniaxial deformation from CT, SEM and NMR: effect of fluids (brine and oil)

Abstract: A systematic microscopic investigation by CT, SEM and NMR to study the effects of brine and oil on rock salt healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Many studies have shown that before the appearance of macro-cracks due to loads, the mechanical properties of materials are affected by local micro-cracks (Chan et al., 1997; Ji et al., 2011; Liu and Su, 2016). According to the hypothesis of strain equivalence, the damage constitutive model of materials can be expressed as follows (Chen, 2020; Lemaitre, 1984; Xie et al., 2020) where trueE˜ is the elastic modulus of damaged materials, E is the elastic modulus of intact materials, and D is the damage variable.…”
Section: Damage Constitutive Model Of Salt Rockmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that before the appearance of macro-cracks due to loads, the mechanical properties of materials are affected by local micro-cracks (Chan et al., 1997; Ji et al., 2011; Liu and Su, 2016). According to the hypothesis of strain equivalence, the damage constitutive model of materials can be expressed as follows (Chen, 2020; Lemaitre, 1984; Xie et al., 2020) where trueE˜ is the elastic modulus of damaged materials, E is the elastic modulus of intact materials, and D is the damage variable.…”
Section: Damage Constitutive Model Of Salt Rockmentioning
confidence: 99%
“…The mechanical properties of salt rock at different loading rates shows some variation. Therefore, it is of great significance to study the mechanical properties of salt rock at different loading rates to ensure the safety and stability of underground gas storage (Chen et al., 2020; Wang et al., 2020a; Wu et al., 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Energy (oil and natural gas) is the material basis for the survival and development of human society, occupying an important strategic position in the national economy [1][2][3]. However, energy reserves in China are relatively small and extremely dependent on foreign countries.…”
Section: Introductionmentioning
confidence: 99%
“…Energy is closely related to economy, environment, and social development [3][4][5]. Especially with the fast development of the economy and the resulting rapid growth of energy consumption [6][7][8][9][10][11][12][13], the need for energy is increasingly growing, especially for fossil energy such as crude oil, leading to the increasing dependence on foreign oil every year [14]. In 2018, China's oil demand exceeded 600 million tons for the first time, and its dependence on foreign countries was close to 70%.…”
Section: Introductionmentioning
confidence: 99%